Economic Dimensions of the Florida Golf Course Industry - John Haydu; Alan Hodges (EDIS, 2002)
Economic impacts of the Florida golf industry were estimated for year 2000 based upon a survey of golf courses, together with other published data and regional economic models. A survey questionnaire was mailed to all 1,334 golf courses in Florida. Responses were received from 223 firms, representing a 17 percent response rate. The respondent golf courses were classified as private (50 percent), semi-private (27 percent), public (14 percent), municipal (nine percent), resort (five percent), and military (one percent). Results for survey respondents were extrapolated to estimate values for the entire industry. This 16-page fact sheet was written by John Haydu and Alan Hodges, and published by the UF Department of Food and Resource Economics, December 2012.